Editorial - Lucy Waldron (Journal of Applied Animal Nutrition)
It’s been a landmark year for the Journal of Applied Animal Nutrition (JAAN)! In the last 12 months we moved publishers (to Wageningen Academic Publishers (WAP) from Cambridge University Press) and I would like to thank all the staff at both these august institutions for their assistance during this transfer. For me, it’s been a time of getting to grips with new software and systems, but this has all settled down well. WAP have been very active in new marketing campaigns, putting out the message of what JAAN is offering to those working in all animal nutrition, which is to provide a platform for publishing both academic and commercial research work in the public domain for all species, including companion animals, wild and zoo species.